Al-Bukhari's Position on the Narrators about whom Ahmad Matruk said in his Book The Great History - Muhammad , Taher (Islamic Sciences Journal, 2023)
ABSTRACT This research is considered one of the researches that deals with the sciences of hadith. , He researches the subject of al-jarh and modification, and knowing the state of the narrators and narrators, and how to take advantage of the words of his elders in this section. And since Ahmad ibn Hanbal was one of the sheikhs of Al-Bukhari, and he preceded him in speaking about the condition of men and their criticism, and the degree of their authenticity and weakness, here Al-Bukhari benefited from his sheikh in criticizing men. Since Ahmad left the hadith of one who does not narrate from him for a reason, as well as those who are close to Ahmad In the scientific rank, this has given Al-Bukhari the preference, in leaving the hadith of the man referring their situation to those before him, not because of Al-Bukhari’s weakness in criticizing men, but because of Al-Bukhari’s keenness in selecting his words in criticizing men, and he has various words in criticizing men, including his saying in Muhammad Bin Muawiyah Al-Basri: There is a view (), and he intended to insult him, and there are many others. I found that Al-Bukhari referred in this way five of the men whom he injured to Ahmed by saying: (Ahmed left him), and after studying their situation it was found that Al-Bukhari had hit the nail on the head, and that they, as Ahmed said, and Al-Bukhari supported him that they left the hadith because of their weakness, or for a hidden reason that he does not know, except for the people of knowledge, the guards of the Sunnah.